The Unspoken Meaning of Names: Cultural Dimensions in Translating Russian Anthroponyms into Indonesian - Lukman, Fahmy; Kartika, Nyai; Machdalena, Susi (Eralingua: Jurnal Pendidikan Bahasa Asing dan Sastra, 2025)
Translating Russian proper names into Indonesian poses linguistic and cultural challenges since Russian anthroponyms, comprising full names, patronymics, and diminutives, encode complex semantic and pragmatic meanings often overlooked in translation. This study aims to examine how these meanings are conveyed in Indonesian literary translations and what cultural implications arise from the process. Using a qualitative descriptive method, data were collected from four Russian literary works translated into Indonesian and analyzed for semantic, pragmatic, communicative, and cultural dimensions. The findings show that most translations fail to reflect the rich social and emotional nuances embedded in Russian anthroponyms. Diminutives, which express intimacy and social bonds, and patronymics, which signify respect and cultural identity, are frequently neutralized or omitted. The study concludes that Indonesian translators tend to prioritize linguistic equivalence over cultural accuracy, leading to the loss of socio-pragmatic depth. This research contributes to cross-cultural translation studies by underscoring the need for culturally sensitive approaches in translating personal names